Dental hygienists' practices and perceptions towards human papillomavirus vaccination: A cross-sectional study in California - Vinodh Bhoopathi; Jeffrey L. Fellows; Beth A. Glenn; Roshan Bastani; Kathryn Ann Atchison (Preventive Medicine Reports)
Objective: The National Human Papillomavirus (HPV) Roundtable urges dental professionals to recommend HPV vaccination for eligible patients. Therefore, this study examined 1) how commonly dental hygienists recommended the HPV vaccine to age-eligible patients, and 2) the factors related to the HPV vaccine recommendation. Methods: In this cross-sectional study, we distributed an online survey to California Dental Hygienists' Association members. The survey data were collected from August to October 2023. Questions were asked about whether they recommended the HPV vaccine for age-eligible individuals and their opinions on recommending the vaccine. We utilized univariate, bivariate, and logistic regression models for our analysis. Results: Only 18 % recommended the HPV vaccine. Nearly 42 % said they lacked time, 60 % lacked sufficient information, and 48 % were unaware of guidelines for counseling on HPV vaccination. Many respondents were uncomfortable (34 %) or unsure (30 %) about recommending the HPV vaccine. Almost 57 % thought they were appropriate healthcare professionals to educate and counsel on HPV-related issues. Those who worked in a dental practice that served all age patients, those who discussed the relationship between HPV and oral cancer, and those with more favorable opinions and attitudes about recommending the HPV vaccine were more likely to recommend the HPV vaccine. Conclusion: Most respondents said they or their team did not recommend the HPV vaccine to eligible patients. Negative views on HPV and the vaccine influenced their recommendation intent. Dental hygienists should stay updated on national HPV vaccination guidelines.